English learning perceptions and career implications: insights from tertiary-level students - Abu El-Haj, Samia A.; El-Haj, Hala Abu; Al-Assaf, Nadia Mustafa (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study investigates students’ perceptions of English language learning at the tertiary level, focusing on its importance for academic success and future career opportunities. The problem addressed is the gap in understanding how students perceive the relevance of English proficiency to their professional futures and the challenges they face in achieving proficiency. A descriptive-analytical and correlational research design was employed, using data from 127 students across various majors and years of study at the University of Jordan, with 122 valid responses. The research utilized a structured questionnaire to explore students’ learning goals, perceived importance of English proficiency, and the challenges they face in language classes. Statistical analysis was applied to identify significant relationships between variables. The major findings reveal that students view English proficiency, particularly in speaking, as critical for their professional futures. However, challenges such as inadequate classroom resources and limited opportunities for practice were commonly reported. The proposed solution emphasizes the need for enhanced language instruction that aligns with students’ professional goals, alongside improvements in classroom infrastructure and more practical language engagement opportunities. The study concludes that addressing these challenges could significantly improve students’ English learning outcomes and better prepare them for their future careers.